2017
DOI: 10.1111/ibi.12512
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific reproduction and disposable soma in an urban population of Common BlackbirdsTurdus merula

Abstract: The mechanism of senescence is an important subject of current research, but our knowledge of the factors influencing the rate of ageing in naturally occurring populations remains rudimentary. Evolutionary theories of senescence predict that investment in reproduction in early life should come at the cost of reduced somatic maintenance and thus result in earlier or more rapid senescence. We use data on the complete reproductive histories of 431 Common Blackbirds (222 males and 209 females) collected during a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…Our study revealed a lower mate fidelity among new adult birds. This is generally in accordance with other studies: partners prefer older, more experienced birds (Choudhury 1995) because the probability of success in such birds is much higher than in young, inexperienced ones (Zhang et al 2015, Jankowiak et al 2017.…”
Section: Pair Fidelity Ratessupporting
confidence: 93%
“…Our study revealed a lower mate fidelity among new adult birds. This is generally in accordance with other studies: partners prefer older, more experienced birds (Choudhury 1995) because the probability of success in such birds is much higher than in young, inexperienced ones (Zhang et al 2015, Jankowiak et al 2017.…”
Section: Pair Fidelity Ratessupporting
confidence: 93%
“…However, several of these studies failed to account for selective disappearance (e.g., Cooch et al, 1992;Flint & Sedinger, 1992;Potti, 1993) and thus complicate the interpretation of individual-vs. population-level effects. Similar to our results, recent longitudinal studies document an increase in egg size in early life, followed by peak and then a late-life decline (Bouwhuis et al, 2009;Jankowiak et al, 2018). The early-life increase in egg size may indicate individual improvement through more efficient foraging abilities, better mate choice, or improved predator avoidance (Forslund & Pärt, 1995).…”
Section: Discussion (1375 Words)supporting
confidence: 90%
“…Life-history theory predicts that fitness trade-offs between current and future reproduction shape inter-specific variation in reproductive strategies observed among iteroparous organisms (Partridge, 1989). To maximize the transfer of their genes to the next generation, individuals adjust their current reproductive investment in light of future reproductive prospects (Jankowiak et al, 2018). The compromise between current and future reproduction enforces tradeoffs between investments in reproduction and other competing functions, such as self-maintenance (Stearns, 1977(Stearns, , 1992Christe et al, 2012).…”
Section: Impact Summary (297 Words)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, individuals that allocate much to reproduction early in life will accumulate a variety of damages that will ultimately cause a shortened life span or an increased rate of reproductive senescence . The central role played by early-vs. late-life trade-offs in the evolution of ageing constitutes the core of the life-history theory of ageing (Kirkwood, 2017) and has been supported by many empirical studies (Hammers, Richardson, Burke, & Komdeur, 2013;Jankowiak, Zyskowski, & Wysocki, 2018). However, most of these studies have focused on females and there is no consensus yet on whether early-vs. late-life trade-offs are prevalent in males.…”
Section: Introductionmentioning
confidence: 99%